3. Trienále Textilu bez Hraníc 2012. - Augustin, Martin; Fekete, Lea (S.l. : Arttex Club of the Textile Artists, 2012)
Adalsteinsdóttir, Málfridur ; Amarger, Brigitte ; Anton, Irene ; Augustín, Andrej ; Bartenberg-Geyer, Gudrun ; Bogdaniené, Eglé Ganda ; Bornemisza, Eszter ; Branišová, Zuzana ; Brett, Alexander ; Brodersen, Anne ; Brooš, Miroslav ; Burns, Barbara ; De Bock, Katy ; Demura, Mieko ; Esser, Barbara ; Horn, Wolfgang ; Fajt, Elena ; Fekete, Lea ; Fernandes, Maria-Theresa ; Fontan, Marie-Noëlle ; Förster, Tim ; Friese, Franziska ; Gaier, Ingrid ; Gunnarsdóttir, Anna ; Hara, Sugane ; Haremska, Danuta ; Holek, Jiří ; Jagerberge-Stängl, Christa ; Jařabáčová, Radana ; Jędrzejec, Anna ; Kaupaite, Birute ; Kirkwood, Fiona ; Kis, Iringó ; Kleszyṅska, Magdalena ; Köder, Mechtildis ; Koizumi, Nobuko ; Kolobarič, Vesna ; Kompánková, Zora ; Kotecka, Agnieszka ; Kovar, Dagmar ; Krotký, Svatoslav ; Kumon, Chiyoka ; Laurinavičiutė, Renata ; May, Ruth ; Morrison, Mary-Anne ; Muller, Nathalie ; Nisonen, Nina ; No, Paula-Jiun ; Nováková Ondreičková, Petra ; Nyberg, Ann ; Ormandíková, Renáta ; Parsons, Brenda ; Pavlik, Josefine ; Polman, Astrid ; Puschner, Marianne ; Rak, Monika ; Rivera, Ernesto ; Schwarz, Tilleke ; Dame Ruth Sirait, Tiarma ; Sláviková, Ivana ; Staňková, Irena ; Suchalová Harichová, L'Ubica ; Szalai, Daniel ; Szklińska, Anna ; Sztetner, Elwira ; Ševčíková Marčeková, Andrea ; Šperková, Blanka ; Takayama, Keiko ; Tammi, Minnamarina ; Tatarová, Lucie ; Tateo, Tiziana ; Těšínská, Jaroslava ; Téxèdre, Coco ; Thurner, Lisa ; Treppo, Mária ; Van der Veen, Grietje ; Véssey, Anna ; Villiger, Erna ; Wakamatsu, Misako ; Wolna, Martyna
boek